Middle powers in Asia Pacific multilateralism a differential framework - Teo, Sarah (Bristol studies in East Asian international relations, 2023)
Drawing on insights from differentiation theory, this book examines the participation of middle powers in multilateralism. Taking Australia, Indonesia and South Korea as examples, it sets out a valuable new framework to explain and understand the behaviour of middle powers in multilateralism